Evaluation of Varnya Mahakashaya Anulepan in Daily Regimen Vis-À-Vis Discoloration for Varna Prasadana - Jangde, Swaranjali; Sharma, Anita; Singh, Rajesh (International Research Journal of Ayurveda & Yoga, 2021)
Skin being the largest organ is very unique in nature as it reflects each and every minute inevitable changes in the body. As it also connects us to the other person firstly, it become very important to have a flawless fresh skin that not only increase the confidence but shows a healthy person from inside, with the increasing lifestyle changes and environmental factor its leading to various pathologies in skin which is affecting its normalcy. To attain a healthy skin and to maintain and prevent from many such pathologies in our classical texts many references has been given along with daily regimen Anulepan has been stated. To evaluate such a reference of Charak Samhita on Varnya Mahakashaya a clinical study has been conducted at Govt Ayurveda College Raipur CG, with 60 randomly selected opd patients. All raw drugs of Varnya Mahakashaya were prepared with Go Ghrita for external application by Shatdhaut process The effects were assessed by a performa before and after and results were analyzed statistically.